2019
DOI: 10.1002/eat.23210
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive eating, but not binge eating or purging, predicts suicidal ideation in adolescents and young adults with low‐weight eating disorders

Abstract: Objective This study examined the relationship between eating‐disorder behaviors—including restrictive eating, binge eating, and purging—and suicidal ideation. We hypothesized that restrictive eating would significantly predict suicidal ideation, beyond the effects of binge eating/purging. Methods Participants were 82 adolescents and young adults with low‐weight eating disorders. We conducted a hierarchical logistic regression, with binge eating and purging in Step 1 and restrictive eating in Step 2, to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
1
19
0
4
Order By: Relevance
“…Given the importance of automatic negative reinforcement in other behaviors, these results suggest individuals might engage in multiple maladaptive behaviors to serve the same function. Future research examining this intriguing possibility could provide insight into whether high comorbidity between restrictive eating and other self-destructive behaviors (Wang et al, 2018(Wang et al, , 2019 reflect shared reinforcement processesand thus, potential shared treatment targets to simultaneously intervene on multiple behaviors. Consistent with this hypothesis, prior real-time monitoring research has found when individuals have thoughts of NSSI, they have simultaneous thoughts of binge eating or purging 10-20% of the time (Nock et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of automatic negative reinforcement in other behaviors, these results suggest individuals might engage in multiple maladaptive behaviors to serve the same function. Future research examining this intriguing possibility could provide insight into whether high comorbidity between restrictive eating and other self-destructive behaviors (Wang et al, 2018(Wang et al, , 2019 reflect shared reinforcement processesand thus, potential shared treatment targets to simultaneously intervene on multiple behaviors. Consistent with this hypothesis, prior real-time monitoring research has found when individuals have thoughts of NSSI, they have simultaneous thoughts of binge eating or purging 10-20% of the time (Nock et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These mixed findings limit the theoretical and clinical understanding of suicide risk in EDs. There is preliminary evidence that focusing on specific features of EDs (e.g., binging, purging, restrictive eating), some of which can occur across many ED diagnoses, may be most informative for understanding suicide risk (Wang et al, 2020). Thus, determining which ED features (rather than diagnoses) most strongly relate to suicide attempts may be a fruitful avenue in helping address limitations and advance knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Mood disorders appear to be the next most common, affecting 17% (Duncombe Lowe et al, ) to 33% (Nicely et al, ) of individuals with ARFID. Despite evidence that suicidality is common among individuals with other eating disorders (Wang et al, n.d.; Franko et al, ), only one study (Duncombe Lowe et al, ) to date has assessed suicidality among individuals with ARFID and did not report the overall prevalence in the sample. Prevalence of neurodevelopmental disorders was 10% in one study (Lieberman et al, ).…”
mentioning
confidence: 99%